Peran Moderasi Ketidaksetaraan Gender pada Pengaruh Pendidikan dan Kesehatan terhadap Pertumbuhan Ekonomi di Negara Berkembang Asia - Budiman, Ilham Febri; Lubis, M. Daffa Fahada (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study aims to analyse the moderating role of gender inequality on the influence of education and health on economic growth in developing Asian countries. The approach used is quantitative with panel data from 32 countries during the period 2014-2023 and analysed using Moderated Regression Analysis (MRA). The research variables include average years of schooling (AYS) for education, life expectancy (LE) for health, the Gender Inequality Index (GII) as the moderating variable, and GDP per capita for economic growth. The results indicate that ALE and HLI have a positive and significant effect on GDP per capita, both partially and simultaneously. Furthermore, the GII does not moderate the effect of ALE on GDP per capita, but significantly moderates the effect of HLI on GDP per capita. This suggests that the effectiveness of health improvements in driving economic growth is influenced by the level of gender equality.